The effect of neoprene shorts on leg proprioception in Australian football players - Cameron, M. L.; Adams, R. D.; Maher, C. G. (Journal of Science and Medicine in Sport, 2008)
Our purpose was to assess the effect of wearing close-fitting neoprene shorts on swinging leg movement discrimination (MD) scores in elite level Australian Football players. Twenty players had their swinging leg MD assessed using the active movement extent discrimination apparatus (AMEDA), once wearing close-fitting neoprene and once wearing loose-fitting running shorts. Subjects were randomly allocated to one of the shorts conditions prior to repeating the test in the other condition. The AMEDA was used to assess the accuracy at which subjects judge the extent of a standing backward swinging leg movement corresponding to the late swing early stance phase of running. Each subject performed 40 movements made to one of five randomly set physical limits, and without the aid of vision made a judgment as to the perceived limit position. From the accuracy of these judgments, a movement discrimination (MD) score was calculated for each subject under each condition. Subjects were grouped as having low or high neuromuscular control, or ability to use proprioception when controlling active movements without vision, based on their loose-shorts MD score. Analysis was performed on the MD scores obtained for each limb from subjects in the two groups, under the two shorts-wearing conditions. There was no main effect of wearing close-fitting shorts when the cohort was treated as a whole. A significant interaction effect was obtained (F = 17.027, p = 0.0006) whereby the mean MD score of the low neuromuscular control ability group was improved when wearing neoprene shorts but was reduced for the high ability group. Wearing close-fitting neoprene shorts has a beneficial effect on leg swing judgment accuracy in subjects with low neuromuscular control ability. Conversely, leg swing judgment accuracy for subjects with high ability was reduced by wearing neoprene shorts.